Cordieritite and Leucogranite Formation during Emplacement of Highly Peraluminous Magma: the El Pilón Granite Complex (Sierras Pampeanas, Argentina) - Rapela, Carlos Washington (2002)
Cordieritites and highly peraluminous granites within the El Pilon granite complex, Sierras Pampeanas, Argentina, were emplaced during a medium-P, high-T metamorphic event during the initial decompression of a Cambrian orogen along the southwestern margin of Gondwana. Very fresh orbicular and massive cordieritite bodies with up to 90% cordieritite are genetically associated with a cordierite monzogranite pluton and a larger body of porphyritic granodiorite. The petrogenesis of this association has been studied using petrographical, mineralogical, thermobarometric, geochemical, geochronological and isotope methods. The granitic magmas were formed by anatexis of mid-crustal metamorphic rocks formed earlier in the Pampean orogeny. The cordieritites appear at the top of feeder conduits that connected the source region located at ∼6 kbar with the pluton emplacement level at 3·7 ± 0·3 kbar. A fall in the liquidus temperature of the melt during emplacement was produced by a marked increase in fluid activity owing to rapid decompression and assimilation of surrounding hydrous metapelitic schists, followed by isobaric crystallization. High-Mg cordierite crystallized early on biotite–sillimanite restitic mineral assemblages of the assimilated schists or at the wall of the feeder conduits. Strong convection in the small magma chamber caused flow segregation of cumulate cordierite and restite, developing leucogranites and highly evolved pegmatoids that are in isotopic equilibrium. Rapid ascent of highly peraluminous magmas might explain why emplacement of these granites was simultaneous with the metamorphic peak registered in neighbouring high-grade migmatite and granulite terranes.